Factors Associated with Healthcare Fraud and Fraud Prevention in Indonesia’s National Health Insurance Hospitals: A PRISMA-Guided Literature Review - Susanna Mutmainnah; Wahyu Sulistiadi (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: This PRISMA-guided literature review synthesizes available evidence on factors associated with fraud risk and fraud-prevention practices in hospitals participating in Indonesia’s National Health Insurance (Jaminan Kesehatan Nasional/JKN) program. Methods: Literature searches were conducted in Scopus, PubMed, and Google Scholar for studies published between 2020 and 2025. A total of six studies (n=6) met the inclusion criteria, consisting of qualitative, quantitative, and socio-legal research designs. Due to heterogeneity in study methods and outcomes, findings were integrated using a thematic literature review approach rather than statistical aggregation. Results: The reviewed studies suggest that fraud-related risks are associated with interacting individual, organizational, and systemic contexts, including financial pressures, coding practices, internal control environments, organizational commitment, information systems, and regulatory implementation factors. Several studies also indicate that strengthened governance mechanisms, such as internal controls and antifraud teams, may support fraud-prevention capacity, although most findings remain perception-based. Overall, the review highlights the need for future empirical research using administrative claims data, audits, and evaluated antifraud interventions to strengthen governance within Indonesia’s national health insurance system. Conclusion: Strengthening governance mechanisms such as internal controls, anti-fraud teams, and integrated claim monitoring systems may support fraud-prevention capacity in JKN hospitals. Nevertheless, the current evidence base remains limited, highlighting the need for future empirical studies using administrative claims data, audits, and evaluated antifraud interventions to improve accountability within Indonesia’s national health insurance system.